Transient spleen enlargement in peripheral blood progenitor cell donors given G-CSF - Heatherman Angela (Journal of Translational Medicine, 2004)
Abstract The administration of granulocyte colony-stimulating factor (G-CSF) to peripheral blood progenitor cell (PBPC) donors causes spleen length to increase, but the duration of enlargement is not known. Eighteen healthy subjects were given 10 μg/kg of G-CSF for 5 days and a PBSC concentrate was collected by apheresis. Ultrasound scans were used to assess craniocaudal spleen length before and after G-CSF administration. Mean spleen length increased from a baseline length of 10.7 ± 1.3 cm to 12.1 ± 1.2 cm on the apheresis day (p < 0.001). Ten days after apheresis, spleen length fell to 10.5 ± 1.2 cm and did not differ from baseline levels (p = 0.57), but in 3 subjects remained 0.5 cm greater than baseline length. Increases in spleen length in PBPC donors are transient and reversible.